IMPLEMENTATION OF THE USE OF QUIZLET BASED ENGLISH LEARNING MEDIA IN CLASS VIII OF MTS NURUL HUDA - Mazyd, Hasim Mazyd; Nopiyadi, Dwi (NextGen Education Review Journal, 2025)
Learning cannot be separated from the application and use of learning media. Quizlet digital flashcard media can be used as an alternative learning media to achieve learning objectives. The problems in this research are: (1) how to implement digital flashcard-based Quizlet learning media in English language learning at MTS Nurul Huda? (2) how to implement digital flashcard-based learning media Quizlet in English language learning at MTS Nurul Huda? (3) what is the impact of implementing digital flashcard-based learning media Quizlet in English language learning at MTS Nurul Huda. This study used qualitative research methods. Research location at MTS Nurul Huda. Data collection techniques in this research used several techniques, namely (1) direct observation, (2) in-depth interviews, (3) documentation. Analysis was carried out using an interactive analysis model. The data validity techniques in this research are technical triangulation and source triangulation. This research is limited to the implementation stage. The instruments in this research consisted of teacher and student interview guidelines. Student interviews/analysis, as well as teacher and student response questionnaires. Media data processing techniques show that the Quizlet flashcards developed obtained a percentage of 83% and 92% so they were included in the 'Very Eligible' category. The teacher and student response questionnaire also showed that the Quizlet flashcard about Degrees of Comparison received a positive response from teachers and students because the percentage of assessment of this media by teachers was 96% and by students was 88% in the 'Very Good' category. Therefore, Quizlet flashcards in the Degree Of Comparison material are suitable for use as an alternative medium for learning English.